2020
DOI: 10.1016/j.cell.2020.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Fine-Scale Organization and Plasticity of the Brain Vasculature

Abstract: Highlights d TubeMap enables fast construction of labeled vascular graphs from TB-sized images d Automated arterio-venous annotations are based on iDISCO+ immunolabeling d We measure regional variations in vessel topology and arterio-venous distances d We study the plasticity of this network in stroke and sensorydeprivation models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
349
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(370 citation statements)
references
References 78 publications
(97 reference statements)
19
349
1
1
Order By: Relevance
“…To ensure correct alignment between channels, we applied a series of rigid and non-rigid registration steps using the Elastix toolbox (Klein et al, 2010) to map the Cux1 and Ctip2 channels onto the TO-PRO-3 channel without inducing non-specific local background warping ( Figure S1). We also found that many of the commonly used programs for performing 3D image stitching (Bria and Iannello, 2012;Hörl et al, 2019) did not accurately align adjacent tile stacks due to spurious stage movement, which has been noted by other groups (Kirst et al, 2020). To ensure accurate image reconstruction, we applied a simplified iterative 2D stitching procedure that uses scale-invariant feature transforms (Lowe, 2004) to produce continuous images without cell duplication along tile edges ( Figure S2).…”
Section: Results Idisco+ Reveals Neuronal Cell-type Deficits In the Tmentioning
confidence: 99%
“…To ensure correct alignment between channels, we applied a series of rigid and non-rigid registration steps using the Elastix toolbox (Klein et al, 2010) to map the Cux1 and Ctip2 channels onto the TO-PRO-3 channel without inducing non-specific local background warping ( Figure S1). We also found that many of the commonly used programs for performing 3D image stitching (Bria and Iannello, 2012;Hörl et al, 2019) did not accurately align adjacent tile stacks due to spurious stage movement, which has been noted by other groups (Kirst et al, 2020). To ensure accurate image reconstruction, we applied a simplified iterative 2D stitching procedure that uses scale-invariant feature transforms (Lowe, 2004) to produce continuous images without cell duplication along tile edges ( Figure S2).…”
Section: Results Idisco+ Reveals Neuronal Cell-type Deficits In the Tmentioning
confidence: 99%
“…In the harmine-exendin-4-treated mice (red line), beta cell volume remains stable during the first month and increases markedly by the end of month 3. Since beta cell mass declines markedly in the first day or days following transplant (8,9), the actual course of events likely resembles the dotted green line. B.…”
Section: Methodsmentioning
confidence: 99%
“…We have used adult human cadaveric islets transplanted into the kidney capsule of immunodeficient NOD-SCID-gamma (NSG) mice (1-3), followed by chronic treatment with a DYRK1A inhibitor (harmine) alone or in combination with a widely used GLP1RA peptide (exendin-4) over one to three months. We have combined this standard animal model with advanced iDISCO + tissue clearing, light-sheet microscopy and 3-D image rendering techniques to quantify human beta cell mass (7,8). We find that harmine and exendin-4 co-administration increases human beta cell mass by a factor of 7fold over three months, without significant alterations in alpha cell mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advancements in tissue clearing technology have brought new breakthroughs in this landscape [1,2,3,4,5,6,7,8,9]. Combined with light-sheet fluorescence microscopy (LSFM) [10] and genetical, viral and immunohistochemical labelling techniques, tissue clearing now enables high-speed volumetric imaging of mammalian (most prominently mouse) brains at cellular resolution [7,11,12,13,14,15,16,17]. Built on top of these technological advancements, we recently reported the construction of CUBIC-Atlas [18], a 3D mouse brain atlas with single cell resolution, where all of the cells in the brain (amounting to approximately 0.1 billion) were digitally analyzed and recorded.…”
Section: Introductionmentioning
confidence: 99%